IDENTIFIKASI KEBUTUHAN PENGGUNA TUNANETRA UNTUK PLATFORM MOBILE MENGGUNAKAN METODE USER PERSONA - DESIGN THINKING - Eko Rahmat Slamet Hidayat Saputra; Arvin Claudy Frobenius (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2022)
In the software development process, it is necessary to use a method that is design thinking. a thought process approach to developing a sustainable human-centered innovation system based on user needs. There are five stages, namely emphasize, define, idea, prototype and test. This research will focus on the emphasize stage, which at this stage will carry out the process of making personas with the user persona technique. The purpose of this research is to design a software system for the visually impaired that is connected to special glasses, namely gablind. The research focuses on identifying and implementing user personas to determine the needs of the visually impaired on the mobile platform and ensuring all activities are validated by the visually impaired. The results of this study are the need for problems faced by the visually impaired by using the user persona technique can be solved properly. With the user persona technique, researchers can find out the need for system development from the perspective and focus on users, namely the visually impaired.